Indigenous Khasa People of Nepal in Crisis - Kafle, Dol Raj (Historical Journal, 2023)
The study relates to the Khasa people, who have lived in Nepal since ancient times and are considered indigenous due to their history of settling and cultivating land in western Nepal. The Khasa people have a rich history dating back to the nomadic period when they migrated from the Caucasus region of Babylonia in West Asia to the Himavatkhaṇḍa and Karnali regions of Western Nepal. However, Hinduization in the Middle Ages and Westernization in modern times has threatened their traditional customs and nature-worshiping religious culture. The purpose of the study is to highlight the identity, tribalism, and current crisis faced by the Khasa people and to advocate for their recognition as indigenous inhabitants of Nepal. Based on secondary sources, this research can guide the state to recognize the Khasa people as indigenous.